Digital System Design with FPGA : Implementation Using Verilog and VHDL - Unsalan, Cem; Tar, Bora (McGraw-Hill's AccessEngineering., 2017)
This practical guide explores the development and deployment of FPGA-based digital systems using the two most popular hardware description languages, Verilog and VHDL. Written by a pair of digital circuit design experts, the book offers a solid grounding in FPGA principles, practices, and applications and provides an overview of more complex topics. Important concepts are demonstrated through real-world examples, ready-to-run code, and inexpensive start-to-finish projects for both the Basys3 and Arty boards.